Investigating the role of lineage in the cortical integration of thalamic inputs - Buchan, M (2022)
Primary sensory cortex receives and integrates inputs from first-order and higher-order thalamic nuclei. First-order inputs convey sensory information from the periphery and exhibit simple response properties, whereas higher-order inputs exhibit more complex response properties, provide contextual feedback, and can modulate first-order inputs. The data presented within this thesis show that the way in which cortical neurons integrate these thalamic inputs, reflects the progenitor cell from which the cortical neurons derive. Within layer 4 of mouse primary somatosensory cortex, excitatory neurons that derive from apical intermediate progenitors exhibit multi-whisker response properties and receive higher-order thalamic input, in a manner consistent with their dendritic morphology. These properties depend upon the expression levels of the transcription factor Lhx2, which when increased, abolishes the higher-order properties of apical intermediate progenitor-derived neurons, and disrupts the induction of sensory-evoked plasticity. These data reveal a lineage- dependent mechanism that establishes the integration and functional contribution of higher-order thalamic inputs within cortex.